Gestational age assessed by optical skin reflection in low-birth-weight newborns: Applications in classification at birth - Vitral, Gabriela Luiza Nogueira; Romanelli, Roberta Maia de Castro; Reis, Zilma Silveira Nogueira; Guimarães, Rodney Nascimento; Dias, Ivana; Mussagy, Nilza; Taunde, Sergio; Neves, Gabriela Silveira; de São José, Carolina Nogueira; Pantaleão, Alexandre Negrão; Pappa, Gisele Lobo; Gaspar, Juliano de Souza; et al. (Frontiers in Pediatrics, 2023)
Introduction: A new medical device was previously developed to estimate gestational age (GA) at birth by processing a machine learning algorithm on the light scatter signal acquired on the newborn's skin. The study aims to validate GA calculated by the new device (test), comparing the result with the best available GA in newborns with low birth weight (LBW). Methods: We conducted a multicenter, non-randomized, and single-blinded clinical trial in three urban referral centers for perinatal care in Brazil and Mozambique. LBW newborns with a GA over 24 weeks and weighing between 500 and 2,500 grams were recruited in the first 24 hours of life. All pregnancies had a GA calculated by obstetric ultrasound before 24 weeks or by reliable last menstrual period (LMP). The primary endpoint was the agreement between the GA calculated by the new device (test) and the best available clinical GA, with 95% confidence limits. In addition, we assessed the accuracy of using the test in the classification of preterm and SGA. Prematurity was childbirth before 37 gestational weeks. Results: Among 305 evaluated newborns, 234 (76.7%) were premature, and 139 (45.6%) were SGA. The intraclass correlation coefficient between GA by the test and reference GA was 0.829 (95%CI: 0.785 – 0.863). However, the new device (test) underestimated the reference GA by an average of 2.8 days (95% limits of agreement: -40.6 to 31.2 days). Its use in classifying preterm or term newborns revealed an accuracy of 78.4% (95%CI: 73.3 - 81.6), with high sensitivity (96.2%; 95%CI: 92.8 - 98.2). The accuracy of classifying SGA newborns using GA calculated by the test was 62.3% (95%CI: 56.6 – 67.8). Discussion: The new device (test) assessed GA at birth in LBW newborns, highly agreeing with the best available GA as a reference. The GA estimated by the device (test), when used to classify newborns on the first day of life, was useful in identifying premature infants but not when applied to identify SGA infants, considering the current algorithm. Nonetheless, the new device (test) has the potential to provide important information in places where the GA is unknown or inaccurate.